The influence of heavy metal pollution on biological properties of soils cities of the Rostov region - Ekaterina Vasilievna Naleta; Olga Anatolievna Kapralova; Sergey Ilich Kolesnikov; Kamil Shagidullovich Kazeev (Наука. Инновации. Технологии, 2022)
We studied the effect of heavy metal pollution on biological properties of soils cities of the Rostov region. Pollution heavy metal soil was recorded in Rostov-on-don, Gu-kovo, Taganrog. In most cases there was a direct relationship between pollutant concentration and the degree of deterioration of the studied soil properties.